Identification of Bacterial Community in Wastewater and Their Kinetic Growth in Microbial Fuel Cells - M. Zain, S.; A. Naa, T.; Suja, F.; A. Zahaimi, N.; N. Baskharan, A. (International Journal of Engineering and Technology, 2019)
Microbial fuel cell (MFC) is an alternative energy system comprise of bio-electrochemical reactor with wastewater as raw material and electrochemically active microorganisms as the main biocatalyst that utilize and convert chemical energy within organic matters to electrical energy. Sequence analysis by BLAST indicated that five species existed which were Pseudomonas aeruginosa, Klebsiella pneumonia, Enterobacter aerogenes, Leucobacter luti and Bacillus cereus. Pseudomonas aeruginosa, Klebsiella pneumonia and Enterobacter aerogenes are biofilm and exoelectrogens that responsible to generate electricity in the MFC for both aerated or with the addition of ferricyanide. However, Leucobacter luti and Bacillus cereus are also among the suspended growth bacteria that can be found in the MFC reactor. As for the rate of removal of COD, it showed that with aerated cathode, the COD removal rate was 51.30 % while with the addition of ferricyanide in the cathode showed a COD removal rate of 93 %. The highest voltage generated by the additional of ferricyanide was 0.841 V while for the aerated cathode, the highest voltage of 0.589 V has been generated. As for the kinetic growth of the bacteria, specific maximum growth rate, Î¼net of the biomass was 0.003 h-1 and 0.004 h-1 for biofilm in the aerated tank while with the addition of ferricyanide, Î¼net for biomass was 0.002 h-1 and 0.001 h-1 for biofilm. Yield growth, Y for biomass in the aerated tank had the highest growth which was 2.035 g.cell/g.substrate while biofilm only had limited growth of 0.1213 g.cell/g.substrate. As for the addition of ferricyanide, Y for biomass was 1.206 g.cell/g.substrate and 0.3268 g.cell/g.substrate for biofilm.Â Â